Antimony trioxide flame-retardant master batch with high impact resistance and preparation method thereof
By preparing high impact-resistant antimony trioxide flame retardant masterbatches, the problems of large mass fluctuations and poor stability in flame retardant modification of ABS resin are solved, and the stability and impact strength of the flame retardant masterbatches are improved, while improving the workshop environmental sanitation.
Patent Information
- Application Number
- CN202510440966.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-09
- Publication Date
- 2025-07-18
AI Technical Summary
In the prior art, the flame retardant modification technology of ABS resin uses powder flame retardant to cause the prepared flame retardant ABS resin to have a large fluctuation in quality, poor stability, and the dust flying affects workers' health.
The flame retardant masterbatch of antimony trioxide is prepared by using high impact resistance through raw materials such as anhydrous ethanol, antimony trichloride, ammonia, deionized water, etc., combined with dispersants, antioxidants and lubricants, to improve the dispersion of antimony trioxide in ABS high-glue powder, reduce mass fluctuations and improve stability.
The prepared flame retardant masterbatch has smooth surface, good stability, high impact strength, stable flame retardant effect, and its performance retention rate is better than that of powder flame retardants under long-term thermal aging experiment and high temperature conditions, improving the workshop environmental sanitation.
Smart Images

Figure CN120329679A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of antimony trioxide flame retardant masterbatches, and specifically relates to a high-impact-resistant antimony trioxide flame retardant masterbatch and a preparation method thereof. Background Art
[0002] Antimony trioxide is a typical additive inorganic flame retardant. Its flame retardant mechanism is that antimony trioxide first melts when heated at the initial stage of the combustion of thermoplastic plastics, forms a protective film on the surface of the thermoplastic plastics, isolates air, reduces the combustion temperature through an endothermic reaction inside, and is oxidized at a high temperature state, diluting the oxygen concentration in the air, thereby achieving a flame retardant effect.
[0003] ABS resin has excellent processing performance, low-temperature resistance, electrical insulation performance, chemical corrosion resistance, high gloss and excellent electroplating performance, and is used in large quantities in the fields of military, automotive, electronic appliances, etc. However, the oxygen index of ABS resin is only 18, belonging to a flammable material. Therefore, antimony trioxide is mostly used as a flame retardant for flame retardant modification to meet the requirements of safe fire prevention.
[0004] Currently, in the prior art, the flame retardant modification technology of ABS resin mainly uses various high-efficiency halogen-containing and antimony-containing substances as main flame retardants, mainly including: decabromodiphenyl ether, octabromodiphenyl ether, tetrabromobisphenol, brominated epoxy oligomer, bromotriazine, decabromodiphenylethane, etc. These flame retardant systems are all powders, and it is easy to bridge during metering and feeding, resulting in large fluctuations in the quality of the prepared flame retardant ABS resin, thus affecting the quality of the final product. At the same time, it causes dust to fly everywhere in the workshop, affecting the physical and mental health of workers. Therefore, a high-impact-resistant antimony trioxide flame retardant masterbatch and a preparation method thereof are proposed to solve the above problems. Summary of the Invention
[0005] (1) Technical Problems to be Solved
[0006] Aiming at the deficiencies of the prior art, the present invention provides a high-impact-resistant antimony trioxide flame retardant masterbatch and a preparation method thereof, which have the advantages of small fluctuations in the quality of the masterbatch, good stability, high impact strength, etc., and solve the problems of large fluctuations in the quality of the prepared flame retardant ABS resin and poor stability in the prior art.
[0007] (2) Technical Solutions
[0008] To achieve the above object of reducing the quality volatility of masterbatch and improving the stability and impact resistance of masterbatch, the present invention provides the following technical solutions: A highly impact-resistant antimony trioxide flame-retardant masterbatch, comprising raw materials in the following weight parts ratio: 100-200 parts of absolute ethanol, 15-45 parts of antimony trichloride, 100-200 parts of ammonia, 50-150 parts of deionized water, 80-100 parts of ABS high rubber powder, 80-100 parts of tetrabromobisphenol, 5-15 parts of dispersant, 5-15 parts of antioxidant, 5-15 parts of lubricant, 5-15 parts of anti-dripping agent.
[0009] Preferably, the mass fractions of the dispersant, antioxidant, lubricant, and anti-dripping agent are all 5%-10%.
[0010] Preferably, it comprises raw materials in the following weight parts ratio: 100 parts of absolute ethanol, 15 parts of antimony trichloride, 100 parts of ammonia, 50 parts of deionized water, 80 parts of ABS high rubber powder, 80 parts of tetrabromobisphenol, 5 parts of dispersant, 5 parts of antioxidant, 5 parts of lubricant, 5 parts of anti-dripping agent.
[0011] Preferably, it comprises raw materials in the following weight parts ratio: 150 parts of absolute ethanol, 30 parts of antimony trichloride, 150 parts of ammonia, 100 parts of deionized water, 90 parts of ABS high rubber powder, 90 parts of tetrabromobisphenol, 10 parts of dispersant, 10 parts of antioxidant, 10 parts of lubricant, 10 parts of anti-dripping agent.
[0012] Preferably, it comprises raw materials in the following weight parts ratio: 200 parts of absolute ethanol, 45 parts of antimony trichloride, 200 parts of ammonia, 150 parts of deionized water, 100 parts of ABS high rubber powder, 100 parts of tetrabromobisphenol, 15 parts of dispersant, 15 parts of antioxidant, 15 parts of lubricant, 15 parts of anti-dripping agent.
[0013] Another technical problem to be solved by the present invention is to provide a preparation method of a highly impact-resistant antimony trioxide flame-retardant masterbatch, comprising the following steps:
[0014] 1) Take 100-200 parts of absolute ethanol and 15-45 parts of antimony trichloride and pour them into a mixing vessel for mixing, then introduce 100-200 parts of ammonia into the mixture to change the pH value of the solution;
[0015] 2) Take the solution in step 1), add distilled water and mix and stir to make it hydrolyze. Put the hydrolyzed solution into a centrifuge for centrifugal separation, then filter the centrifuged solution to obtain the precipitate of the solution, wash the precipitate with 50-150 parts of deionized water, and place the washed precipitate in an oven at 110-120°C for drying to obtain antimony trioxide for standby;
[0016] 3) Take 80 - 100 parts of ABS high - rubber powder, 80 - 100 parts of tetrabromobisphenol, 5 - 15 parts of lubricant, 5 - 15 parts of dispersant and the antimony trioxide obtained in step 2) and mix them. Pour the mixture into a high - speed mixer and blend for 15 - 25 min;
[0017] 4) When blending the mixture in step 3), add 5 - 15 parts of antioxidant and 5 - 15 parts of anti - dripping agent in small amounts and multiple times;
[0018] 5) Pour the mixture in step 4) into a twin - screw extruder, granulate the mixture through the extruder, and place the particles produced by the twin - screw extruder in an oven at 80 - 100 °C for drying for 4 - 6 h to obtain the flame - retardant masterbatch. Among them, the temperature of the twin - screw extruder is controlled at 180 - 200 °C, the rotation speed of the screw is controlled at 100 - 200 r / min, and the rotation speed of the feeder is controlled at 50 - 100 r / min.
[0019] (III) Beneficial effects
[0020] Compared with the prior art, the present invention provides a high - impact - resistant antimony trioxide flame - retardant masterbatch and its preparation method, which have the following beneficial effects:
[0021] The high - impact - resistant antimony trioxide flame - retardant masterbatch has a round and smooth surface without obvious abnormal heterochromatic points. Using this flame - retardant masterbatch to prepare flame - retardant ABS will not pollute the workshop environment during processing, thus protecting the physical and mental health of workers. Compared with the traditional technology, the dispersant is used to improve the dispersion of antimony trioxide in the ABS high - rubber powder, obtaining modified plastic particles with more stable quality. The performance of the flame - retardant masterbatch is more stable, the product quality fluctuation is small, and it has the advantages of good flame - retardant stability, high impact strength, and no obvious influence on other properties. The flame - retardant ABS prepared by this flame - retardant masterbatch has better retention rates of various mechanical properties than the flame - retardant ABS prepared by using powder flame - retardants under long - term thermal aging test conditions, and it also has better yellowing resistance at high temperatures. Brief description of the drawings
[0022] Figure 1 It is a schematic diagram of the comparative analysis of the physical and chemical properties of a high - impact - resistant antimony trioxide flame - retardant masterbatch FRMHR1 S and an existing flame - retardant masterbatch FRMHR1 proposed by the present invention;
[0023] Figure 2 It is a digital schematic diagram of a high - impact - resistant antimony trioxide flame - retardant masterbatch FRMHR1 S and an existing flame - retardant masterbatch FRMHR1 proposed by the present invention;
[0024] Figure 3 It is an infrared spectrum comparison schematic diagram of a high - impact - resistant antimony trioxide flame - retardant masterbatch FRMHR1 S and an existing flame - retardant masterbatch FRMHR1 proposed by the present invention;
[0025] Figure 4 Schematic diagram for comparative analysis of long-term thermal aging performance between a highly impact-resistant antimony trioxide flame retardant masterbatch FRMHR1 S proposed by the present invention and an existing flame retardant masterbatch FRMHR1;
[0026] Figure 5 Digital schematic diagram of a highly impact-resistant antimony trioxide flame retardant masterbatch FRMHR1 S proposed by the present invention and an existing flame retardant masterbatch FRMHR1 baked at 180 °C for different times. Detailed implementation mode
[0027] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative work shall fall within the protection scope of the present invention.
[0028] Embodiment 1: A highly impact-resistant antimony trioxide flame retardant masterbatch, comprising the following raw materials in parts by weight: 100 parts of absolute ethanol, 15 parts of antimony trichloride, 100 parts of ammonia gas, 50 parts of deionized water, 80 parts of ABS high rubber powder, 80 parts of tetrabromobisphenol, 5 parts of dispersant, 5 parts of antioxidant, 5 parts of lubricant, and 5 parts of anti-dripping agent.
[0029] The mass fractions of the dispersant, antioxidant, lubricant, and anti-dripping agent are all 5%.
[0030] A preparation method of a highly impact-resistant antimony trioxide flame retardant masterbatch, comprising the following steps:
[0031] 1) Take 100 parts of absolute ethanol and 15 parts of antimony trichloride and pour them into a mixing vessel for mixing, and then introduce 100 parts of ammonia gas into the mixture to change the pH value of the solution;
[0032] 2) Take the solution in step 1), add distilled water and mix and stir to make it hydrolyze. Put the hydrolyzed solution into a centrifuge for centrifugal separation, and then filter the centrifuged solution to obtain the precipitate of the solution. Wash the precipitate with 50 parts of deionized water, and place the washed precipitate in an oven at 110 °C for drying to obtain antimony trioxide for standby;
[0033] 3) Take 80 parts of ABS high rubber powder, 80 parts of tetrabromobisphenol, 5 parts of lubricant, 5 parts of dispersant and the antimony trioxide obtained in step 2) for mixing, and pour the mixture into a high-speed mixer for blending for 15 min;
[0034] 4) When blending the mixture in step 3), add 5 parts of antioxidant and 5 parts of anti-dripping agent in small amounts and multiple times;
[0035] 5) Pour the mixture in step 4) into a twin-screw extruder, granulate the mixture through the extruder, and place the particles produced by the twin-screw extruder in an oven at 80 °C for drying for 4 h to obtain the flame retardant masterbatch. Among them, the temperature of the twin-screw extruder is controlled at 180 °C, the rotation speed of the screw is controlled at 100 r / min, and the rotation speed of the feeder is controlled at 50 r / min.
[0036] Example 2: A high-impact antimony trioxide flame retardant masterbatch, comprising the following raw materials in parts by weight: 150 parts of absolute ethanol, 30 parts of antimony trichloride, 150 parts of ammonia gas, 100 parts of deionized water, 90 parts of ABS high rubber powder, 90 parts of tetrabromobisphenol, 10 parts of dispersant, 10 parts of antioxidant, 10 parts of lubricant, and 10 parts of anti-dripping agent.
[0037] The mass fractions of the dispersant, antioxidant, lubricant, and anti-dripping agent are all 7.5%.
[0038] A preparation method of a high-impact antimony trioxide flame retardant masterbatch, comprising the following steps:
[0039] 1) Take 150 parts of absolute ethanol and 30 parts of antimony trichloride and pour them into a mixing vessel for mixing, then introduce 150 parts of ammonia gas into the mixture to change the pH value of the solution;
[0040] 2) Take the solution in step 1), add distilled water and mix and stir to make it hydrolyze. Put the hydrolyzed solution into a centrifuge for centrifugal separation, then filter the centrifuged solution to obtain the precipitate of the solution, wash the precipitate with 100 parts of deionized water, and place the washed precipitate in an oven at 115 °C for drying to obtain antimony trioxide for standby;
[0041] 3) Take 90 parts of ABS high rubber powder, 90 parts of tetrabromobisphenol, 10 parts of lubricant, 10 parts of dispersant and mix them with the antimony trioxide obtained in step 2), and pour the mixture into a high-speed mixer for blending for 20 min;
[0042] 4) When blending the mixture in step 3), add 10 parts of antioxidant and 10 parts of anti-dripping agent in small amounts and multiple times;
[0043] 5) Pour the mixture in step 4) into a twin-screw extruder, granulate the mixture through the extruder, and place the particles produced by the twin-screw extruder in an oven at 90 °C for drying for 5 h to obtain the flame retardant masterbatch. Among them, the temperature of the twin-screw extruder is controlled at 190 °C, the rotation speed of the screw is controlled at 150 r / min, and the rotation speed of the feeder is controlled at 75 r / min.
[0044] Example 3: A highly impact-resistant antimony trioxide flame retardant masterbatch, comprising raw materials in the following parts by weight: 200 parts of absolute ethanol, 45 parts of antimony trichloride, 200 parts of ammonia gas, 150 parts of deionized water, 100 parts of ABS high rubber powder, 100 parts of tetrabromobisphenol, 15 parts of dispersant, 15 parts of antioxidant, 15 parts of lubricant, and 15 parts of anti-dripping agent.
[0045] The mass fractions of the dispersant, antioxidant, lubricant, and anti-dripping agent are all 10%.
[0046] A preparation method of a highly impact-resistant antimony trioxide flame retardant masterbatch, comprising the following steps:
[0047] 1) Take 200 parts of absolute ethanol and 45 parts of antimony trichloride and pour them into a mixing vessel for mixing, then introduce 200 parts of ammonia gas into the mixture to change the pH value of the solution;
[0048] 2) Take the solution in step 1), add distilled water and mix and stir to hydrolyze it. Put the hydrolyzed solution into a centrifuge for centrifugal separation, then filter the centrifuged solution to obtain the precipitate of the solution, wash the precipitate with 150 parts of deionized water, and place the washed precipitate in an oven at 120 °C for drying to obtain antimony trioxide for standby;
[0049] 3) Take 100 parts of ABS high rubber powder, 100 parts of tetrabromobisphenol, 15 parts of lubricant, 15 parts of dispersant and the antimony trioxide obtained in step 2) for mixing, and pour the mixture into a high-speed mixer for blending for 25 min;
[0050] 4) When blending the mixture in step 3), add 15 parts of antioxidant and 15 parts of anti-dripping agent in small amounts and multiple times;
[0051] 5) Pour the mixture in step 4) into a twin-screw extruder, granulate the mixture through the extruder, and place the particles produced by the twin-screw extruder in an oven at 100 °C for drying for 6 h to obtain the flame retardant masterbatch. Among them, the temperature of the twin-screw extruder is controlled at 200 °C, the rotation speed of the screw is controlled at 200 r / min, and the rotation speed of the feeder is controlled at 100 r / min.
[0052] Please refer to Figure 1 , conduct tensile property test, flexural property test, cantilever beam notched impact strength vertical burning property test on the prepared flame retardant masterbatch, and compare it with the masterbatch prepared by the prior art. The experimental conditions are temperature 220 °C, load 10 kg. For each type of test, four groups of existing flame retardant masterbatch FRMHR1 and four groups of flame retardant masterbatch FRMHR1 S prepared by the technology are set for comparison. The comparison results are as Figure 1 shown:
[0053] From the overall data, the particles prepared using flame retardant masterbatch have more stable performance, with less product quality fluctuation. In particular, the impact strength and flame retardant effect are significantly better than those of the corresponding powders, while other physical and chemical properties remain unchanged. This is because the powder flame retardant tetrabromobisphenol, especially the powder flame retardant synergist antimony trioxide, is prone to agglomeration, and at the same time, bridging is likely to occur during feeding, resulting in uneven dispersion in the matrix resin, thus affecting the flame retardant stability of the product. Further confirmation from the specific gravity in the figure shows that when increasing the addition amount of the powder flame retardant, the specific gravity of the obtained modified plastic particles does not increase accordingly, but shows irregular fluctuations. When using the flame retardant masterbatch, the dispersion of the flame retardant in it is effectively improved, so modified plastic particles with more stable quality are obtained.
[0054] Please refer to Figure 2-3 , the characteristic peaks of the infrared spectra of the two masterbatches indicate that the chemical structure of the tetrabrominated flame retardant and its flame retardant system compounded with antimony white does not change after being made into the flame retardant masterbatch, indicating that the preparation of the masterbatch does not affect the performance of the flame retardant, while effectively improving the dispersion state of the flame retardant system in it. In addition, from Figure 2 it can be seen that the particle sizes of the prepared masterbatch particles are not particularly uniform, but the particle morphologies are relatively full, the surfaces are smooth, and there are no obvious variegated spots.
[0055] Please refer to Figure 4-5 , further conduct a long-term thermal aging experiment on the 1# and 5# modified flame retardant ABS products with the same formula in an 80°C oven. The obtained data are as Figure 4 shown, and then combined with the photos taken after baking at 180°C for different times as Figure 5 shown. From Figure 4 it can be seen that for the flame retardant ABS prepared using the flame retardant masterbatch during the long-term thermal aging experiment at 80°C, the retention rate of its flame retardant performance is significantly better than that of the flame retardant ABS prepared using the flame retardant powder. At the same time, the retention rates of other mechanical properties are also better than those of the flame retardant ABS prepared with the powder. This is because when using the flame retardant masterbatch, in addition to better dispersion of the flame retardant in the matrix resin, its interfacial adhesion in the matrix resin is stronger than that of the powder in the matrix resin, resulting in better retention rates of its various physical and chemical properties under long-term thermal aging conditions. At the same time, for the photos of the flame retardant masterbatch baked at 180°C for different times in Figure 5 , a, b, c, d in it are the digital photos of the flame retardant ABS samples prepared with the flame retardant masterbatch baked for 10, 20, 30, and 60 minutes respectively, while Figure 5Among them, a, b, c, and d are digital photos of flame-retardant ABS specimens prepared with flame-retardant powder under the same conditions when baked for 10, 20, 30, and 60 minutes respectively. It can be seen that the flame-retardant ABS prepared with the flame-retardant masterbatch does not show obvious color change after being baked at 180°C for 1 hour, while the flame-retardant ABS prepared with the powder flame-retardant turns significantly yellow after being baked at 180°C for less than 20 minutes. It can be seen that the flame-retardant ABS prepared with the flame-retardant masterbatch has better yellowing resistance performance.
[0056] In summary, the surface of the flame-retardant masterbatch and its compounded flame-retardant masterbatch particles is round, smooth, and has no obvious foreign-colored spots. At the same time, when using this flame-retardant masterbatch to prepare flame-retardant ABS, in addition to improving the workshop working environment, the prepared flame-retardant ABS has the following two characteristics. Compared with the flame-retardant ABS prepared with the powder flame-retardant, the flame-retardant prepared with the prepared flame-retardant masterbatch has more stable flame-retardancy, better flame-retardant effect, significantly improved impact strength, and no obvious influence on other properties. Under the conditions of long-term thermal aging experiments, the retention rates of various mechanical properties of the flame-retardant ABS prepared with this flame-retardant masterbatch are better than those of the flame-retardant ABS prepared with the powder flame-retardant. At the same time, it has more excellent yellowing resistance performance under high-temperature conditions.
[0057] In addition, in the prior art, the hydrolysis of the cycloester is in a sulfuric acid / glacial acetic acid system. In this system, glacial acetic acid volatilizes and a large amount of acidic water is discharged during the production process, resulting in obvious environmental pollution. In the technology of this application, condensation is carried out first and then hydrolysis, avoiding the hydrolysis phenomenon of fluorine at the C-10 position. Therefore, the left-fluorocycloester can be conveniently hydrolyzed with a dilute alkali aqueous solution, thereby greatly reducing the hydrolysis cost while avoiding a large amount of environmental pollution in the original operation process.
[0058] Although the embodiments of the present invention have been shown and described, for those of ordinary skill in the art, it can be understood that various changes, modifications, substitutions, and variations can be made to these embodiments without departing from the principles and spirit of the present invention. The scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A high impact-resistant antimony trioxide flame retardant masterbatch, characterized in that, The raw materials include the following parts by weight: 100 - 200 parts of absolute ethanol, 15 - 45 parts of antimony trichloride, 100 - 200 parts of ammonia gas, 50 - 150 parts of deionized water, 80 - 100 parts of ABS high rubber powder, 80 - 100 parts of tetrabromobisphenol, 5 - 15 parts of dispersant, 5 - 15 parts of antioxidant, 5 - 15 parts of lubricant, and 5 - 15 parts of anti - dripping agent.
2. The flame retardant masterbatch of antimony trioxide with high impact resistance according to claim 1, characterized in that, The mass fractions of the dispersant, antioxidant, lubricant, and anti - dripping agent are all 5% - 10%.
3. A high impact-resistant antimony trioxide flame retardant masterbatch according to claim 1, characterized in that, The raw materials include the following parts by weight: 100 parts of absolute ethanol, 15 parts of antimony trichloride, 100 parts of ammonia gas, 50 parts of deionized water, 80 parts of ABS high rubber powder, 80 parts of tetrabromobisphenol, 5 parts of dispersant, 5 parts of antioxidant, 5 parts of lubricant, and 5 parts of anti - dripping agent.
4. A high impact resistant antimony trioxide flame retardant masterbatch according to claim 1, characterized in that, The raw materials include the following parts by weight: 150 parts of absolute ethanol, 30 parts of antimony trichloride, 150 parts of ammonia gas, 100 parts of deionized water, 90 parts of ABS high rubber powder, 90 parts of tetrabromobisphenol, 10 parts of dispersant, 10 parts of antioxidant, 10 parts of lubricant, and 10 parts of anti - dripping agent.
5. A high impact resistant antimony trioxide flame retardant masterbatch according to claim 1, characterized in that, The raw materials include the following parts by weight: 200 parts of absolute ethanol, 45 parts of antimony trichloride, 200 parts of ammonia gas, 150 parts of deionized water, 100 parts of ABS high rubber powder, 100 parts of tetrabromobisphenol, 15 parts of dispersant, 15 parts of antioxidant, 15 parts of lubricant, and 15 parts of anti - dripping agent.
6. A preparation method of a high impact-resistant antimony trioxide flame retardant masterbatch, characterized in that, It includes the following steps: 1) Take 100 - 200 parts of absolute ethanol and 15 - 45 parts of antimony trichloride and pour them into a mixing vessel for mixing. Then, introduce 100 - 200 parts of ammonia gas into the mixture to change the pH value of the solution. 2) Take the solution from step 1), add distilled water and mix and stir to make it hydrolyze. Put the hydrolyzed solution into a centrifuge for centrifugal separation. Then, filter the centrifuged solution to obtain the precipitate of the solution, wash the precipitate with 50 - 150 parts of deionized water, and place the washed precipitate in an oven at 110 - 120 °C for drying to obtain antimony trioxide for standby. 3) Take 80 - 100 parts of ABS high rubber powder, 80 - 100 parts of tetrabromobisphenol, 5 - 15 parts of lubricant, 5 - 15 parts of dispersant and the antimony trioxide obtained in step 2) for mixing, and pour the mixture into a high - speed mixer for blending for 15 - 25 min. 4) When blending the mixture in step 3), add 5 - 15 parts of antioxidant and 5 - 15 parts of anti - dripping agent in small amounts and multiple times. 5) Pour the mixture in step 4) into a twin - screw extruder, granulate the mixture through the extruder, and place the particles produced by the twin - screw extruder in an oven at 80 - 100 °C for drying for 4 - 6 h to obtain the flame - retardant masterbatch. Among them, the temperature of the twin - screw extruder is controlled at 180 - 200 °C, the rotation speed of the screw is controlled at 100 - 200 r / min, and the rotation speed of the feeder is controlled at 50 - 100 r / min.